Efectos de un programa de telerehabilitación sobre la funcionalidad en personas mayores - Mc- Ardle Draguicevic, Nelson Fabian; Rubén Loncon; Valeria Elizama; Nelson Mc Ardle-Draguicevic; Igor Cigarroa (My University, 2022)
Objective: To determine the effects of a telerehabilitation (TR) program on the level of functional independence and the number of falls in older people attending a day care center. Materials and method: 14 older people (x̄ = 74 years), submitted to a kinesitherapy / physiotherapy / physical therapy (PT) program through telerehabilitation for a period of 12 weeks. The control group received educational intervention through a physical activity booklet which they had to develop independently, with weekly telephone supervision, while the experimental group received 15 kinesitherapy / physiotherapy / physical therapy sessions via video calls through WhatsAppTM application. Both groups were evaluated pre and post intervention with the Barthel index scale (BI) and the number of falls using the comprehensive geriatric assessment (CGA). Results: The experimental group increased the Barthel index scale score (↑3,6) while the control group decreased this score (↓6,9). Both groups decreased the number of falls, without differences between groups. When comparing both groups, the elderly who underwent a kinesitherapy / physiotherapy / physical therapy program through telerehabilitation showed significantly greater improvements in Barthel index scale than the control group (p <0.05). Conclusion: Older people who participated in a kinesitherapy / physiotherapy / physical therapy program through telerehabilitation presented a higher level of functional independence compared to participants in the intervention with a phone call-guided physical activity booklet, which suggests a telerehabilitation programs as an alternative therapeutics to improve the level of independence in older people. Keywords: Elderly; Telerehabilitation; Independent Living; Accidental Falls; Clinical Trial
Keywords: None